Il n’y a pas de normes sexuelles. Il n’y a que des normes sociales » - Aurélie Pfauwadel (Genre, Sexualité et Société)
At the time of The Will to Knowledge, Foucault saw psychoanalysis as a “science-aveu” that would fully support the project of constituting a scientia sexualis. Our perspective holds, on the contrary, that Lacan’s originality consists in maintaining that there is no knowledge on sex, that sexuality pierces a hole in the real and in knowledge. The unconscious and the various discourses constitute responses to this hole in order to make up for “the absence of sexual relation” through the intermediary of semblance and makeshift solutions that are always singular. Throughout his teaching, Lacan sought to conceptualize the conditions for the possibility of a discourse and a practice outside of the norms.A growing number of psychoanalysts have been drawing on Foucault in order to demonstrate a certain compatibility between psychoanalysis and gender studies. This article takes a counter-stance by seeking to demonstrate that psychoanalysis in itself has at its disposal the means to think through its conditions of possibility and to avoid the pitfalls of normativity.